Gastric mucin phenotype indicates aggressive biological behaviour in early differentiated gastric adenocarcinomas following endoscopic treatment - Kai Song; Qi Yang; Yu Yan; Xiaoyan Yu; Kanlun Xu; Jinghong Xu (BMC, 2021)
Abstract Background The distribution of mucin phenotypes and their relationship with clinicopathological features in early differentiated gastric adenocarcinomas in a Chinese cohort are unknown. We aimed to investigate mucin phenotypes and analyse the relationship between mucin phenotypes and clinicopathological features, especially biological behaviours, in early differentiated gastric adenocarcinomas from endoscopic specimens in a Chinese cohort. Methods Immunohistochemical staining of CD10, MUC2, MUC5AC, and MUC6 was performed in 257 tissue samples from patients with early differentiated gastric adenocarcinomas. The tumour location, gross type, tumour size, histological type, depth of invasion, lymphovascular invasion, mucosal background and other clinicopathological parameters were evaluated. The relationship between mucin phenotypes and clinicopathological features was analysed with the chi-square test. Results The incidences of gastric, gastrointestinal, intestinal and null phenotypes were 21 %, 56 %, 20 and 3 %, respectively. The mucin phenotypes were related to histology classification (P < 0.05). The proportion of the gastric phenotype became greater during the transition from differentiated to undifferentiated (P < 0.05). Complete intestinal metaplasia was higher in the gastric and intestinal phenotypes than in the gastrointestinal phenotype (P < 0.05). Tumours with poorly differentiated adenocarcinoma were mainly of the gastric phenotype, which was significantly higher than that of purely differentiated tubular adenocarcinoma (P < 0.05), and the depth of invasion in the mixed type was deeper (P < 0.05). Neither recurrence nor metastasis was detected. Conclusions The mucin phenotype of early-differentiated gastric adenocarcinoma has clinical implications, and the gastric phenotype has aggressive biological behaviour in early differentiated gastric cancers, especially in those with poorly differentiated adenocarcinoma or papillary adenocarcinoma components.